Comparison of heath communities from the class Nardo-Callunetea from the Toruń Basin and other regions of Poland - Chojnacka, Joanna; Cyzman, Wiesław; Nienartowicz, Andrzej; Deptuła, Miłosz (Ecological Questions, 2010)
This paper presents the variability within two heath associations, i.e. Pohlio-Callunetum and Arctostaphylo-Callunetum in the territory of Poland. The variability of the former syntaxon was determined based on 9 sets of published relevés, made in different regions of Poland. In the case of the latter syntaxon, there were 13 sets of relevés. The sets were being compared in respect of species composition assuming the degrees of species constancy as characteristics of the compared sets. The comparisons have been done with the classic phytosociological method according to Braun-Blanquet, as well as with numerical taxonomy methods using the software MVSP. In both cases, the subsets of relevés from the artillery range near the city of Toruń were clearly separated from the others. In the obtained dendrograms, relevés from the neighbourhood of Toruń, classified within the analysed subassociations formed separate clusters and their distance to other groups of relevés from the same association but from different regions of Poland was significant. Both in the case of the association Pohlio Callunetum and the association Arctostaphylo-Callunetum, sets of relevés from the Skwierzyna (coniferous) Forest in western Poland and from the Tuchola Forest in northern Poland were the most similar to relevés from the neighbourhood of Toruń.